PERENCANAAN PLTA UNDIP II, SEMARANG - Yudhi Putra Wira Negara; Cahyarsi Murtiaji; Joetata Hadihardaja; Sri Sangkawati (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2013)
Diponegoro University as an educational institution has an important role as a contribution and dedication to the community in the conservation and development of water resources. With the location of the campus UNDIP Tembalang located in high elevation areas, plus there is a river flowing in front of the campus UNDIP, supported by intellectual property owned civitas academy UNDIP then the potential is more than enough to mengembangangkan and utilize all its potential for the benefit of conservation of water resources and hydropower plant. Hydroelectric power (hydropower) is one of the power plants that use renewable energy in the form of water. One advantage of this generator is a fast response so it is suitable for peak load conditions or when there is interference in the network. In addition to the output power capacity of the greatest among other renewable energy, hydro power has also been there since time immemorial. Debit design of UNDIP II Hidropower Plant Semarang using the mass inflow curve for 11 years (2001 s/d 2011) the results was 0.152 m3/second,, but to get the most power capacity used 0.220 m3/second discharge of hydrologic analysis calculations. Design structures to support the planned hydropower operations in order to function properly is building decision (Intake), rapid pipe, door arrangements, turbine, sewer, and draft tube. The results of the planning details are as follows: (1) using a type intake tower with a diameter of 0.83 m at an elevation of +147.05 (2) Penstock with a diameter of 0.83 m and a total length of 150 m and is connected to the intake hole at an elevation of +139 , 00. (3) High net falls 42.25 m. (4) The power generated by 77,51 kW. (5) door controller using 500x250x10 Canal profiles. (6) used the Turbine Turbine type Francis. (7) The sewer masonry trapezoidal cross section times the size of b = 0.7 m, h = 0.4 m. Review and Planning UNDIP II Hydropower plant cost of Rp 56.857.829.520.98 (fifty-six billion, eight hundred and fifty-seven million eight hundred twenty nine thousand five hundred twenty dollars) with a long time of the 25 weeks.